2018
DOI: 10.1016/j.afjem.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Acute mesenteric ischaemia: A case of expedited diagnosis and management using point-of-care ultrasound

Abstract: IntroductionThe term acute abdomen refers to a clinical syndrome of sudden onset, severe abdominal pain. The differential diagnosis for this presentation is broad, but most cases require emergent medical or surgical management. Especially in cases of ischaemic bowel, time to diagnosis can mean the difference between survival and death. As a result, mortality remains high in resource-limited settings.Case reportWe describe the case of a 28-year-old male who presented to an urban Ethiopian emergency centre with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Soundappan SV 18 in his research work found the diagnostic precision and clinical effectiveness of the surgeon-performed FAST among pediatric patients of BAT. 19 Two other research works concluded that FAST performed by surgeon for blunt abdominal trauma was a secure and precise with high rate of specificity. 20,21…”
Section: Discussionmentioning
confidence: 98%
“…Soundappan SV 18 in his research work found the diagnostic precision and clinical effectiveness of the surgeon-performed FAST among pediatric patients of BAT. 19 Two other research works concluded that FAST performed by surgeon for blunt abdominal trauma was a secure and precise with high rate of specificity. 20,21…”
Section: Discussionmentioning
confidence: 98%
“…По можливості слід розглянути первинний анастомоз. У випадку створення стоми лише життєздатність стоми може ввести в оману, оскільки деякі віддалені ділянки можуть бути вражені тим самим патологічним процесом [24] Висновки Після резекції тонкої кишки у випадку несудинної етіології, перевагу варто надати міжкишковому анастомозу або Y-подібному анастомозу за Майдлем.…”
Section: результати дослідження та їх обговоренняunclassified